The World Bank Group Sanctions Process and Its Recent Reforms - Leroy, Anne-Marie; Fariello, Frank (World Bank, 2012)
The World Bank is one of the world's premier international financial institutions. It provides low-interest loans, interest-free credits, and grants to developing countries for a wide array of purposes that include investments in education, health, public administration, infrastructure, financial and private sector development, agriculture, and environmental and natural resource management, with aggregate new lending commitments of approximately $60 billion and aggregate outstanding loans and credits of $230 billion in Fiscal Year 2010. With the financial support provided by the Bank, borrowers implement projects and programs, including the procurement of goods, works, and services necessary to carry out the project or program activities. The study begins by outlining the principal features of the Bank Group's sanctions process as it exists today (part two) and sketches some the key consideration underlying reform of the Bank's sanctions process (part three). It then describes how those considerations have influenced the historical evolution of the sanctions process (part four), with particular focus on the recent changes that the Bank has adopted to improve the efficiency, effectiveness, and procedural of that process (part five). Finally, it concludes by reflecting on some of the longer-term implications of the reform process to date (part six).